2007
DOI: 10.1037/1082-989x.12.4.451
|View full text |Cite|
|
Sign up to set email alerts
|

Twins and the study of rater (dis)agreement.

Abstract: Genetically informative data can be used to address fundamental questions concerning the measurement of behavior in children. The authors illustrate this with longitudinal multiplerater data on internalizing problems in twins. Valid information on the behavior of a child is obtained for behavior that multiple raters agree upon and for rater-specific perception of the child's behavior. Rater-disagreement variance 2 (rd) accounted for 35% of the individual differences in internalizing behavior. Up to 17% of this… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
98
0
1

Year Published

2008
2008
2017
2017

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 74 publications
(104 citation statements)
references
References 44 publications
5
98
0
1
Order By: Relevance
“…This may be relevant to our analyses, as some studies suggest that parents may be relatively insensitive to the more covert internalizing problems of children (Seiffge-Krenke and Kollmar 1998;Ollendick and King 1994). A previous longitudinal multiple rater study in our sample found that rater disagreement variance accounted for 35% of the individual differences in internalizing problems (Bartels et al 2007a).…”
Section: Introductionmentioning
confidence: 86%
See 2 more Smart Citations
“…This may be relevant to our analyses, as some studies suggest that parents may be relatively insensitive to the more covert internalizing problems of children (Seiffge-Krenke and Kollmar 1998;Ollendick and King 1994). A previous longitudinal multiple rater study in our sample found that rater disagreement variance accounted for 35% of the individual differences in internalizing problems (Bartels et al 2007a).…”
Section: Introductionmentioning
confidence: 86%
“…Unlike the WB syndrome scale of the CBCL, the broad band internalizing scale that it is part of, has received a fair amount of attention in the field of behavior genetics. Longitudinal studies in our Dutch twin sample suggested increasing influence of the shared environment and decreasing genetic effects between the age of 3 and 12 years (Van der Valk et al 2003a;Bartels et al 2004bBartels et al , 2007a. Exploring the relative influence of genes and environment on behavioral stability, Bartels et al (2004b) found that both genes (average influence 43%) and shared environment (average influence 47%) had a major impact on the continuity of internalizing problems over time.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…These authors argue that studies that focus on the correlation between the parents ratings or between parent and teacher ratings may be missing major discrepancies as the correlation only relates how closely the patterns match not the level or severity of the problems being reported by the informants (Treutler & Epkins, 2003). In a longitudinal study on the internalizing behaviors of twins in the Netherlands, rater disagreement was found to be substantial and the authors stated that rater bias may be persistent over several months to years and can significantly affect the results of longitudinal studies (Bartels, Boomsma, Hudziak, Beijsterveldt, & van den Oord, 2007).…”
Section: Academy Of Pediatrics [Aap] 2000)mentioning
confidence: 99%
“…However, this may led to correlated measurement errors which are reflected in the C component in the genetic modelling (Bartels et al, 2007b). Such a form of rater bias could explain part of the estimated common environmental influences on testis size.…”
Section: Heritability Of Testis Sizementioning
confidence: 99%